The Impact of Organizational Culture, Work Environment, and Wage Levels on Employee Performance in SMEs in Indonesia - Amas Lahat, Mohammad; Sabil, Sabil; ., Rosento; Suratriadi, Panji; Sari Marthanti, Amas (Dinasti Publisher, 2024)
This study aims to analyze the impact of Organizational Culture, Work Environment, and Wage Level on Employee Performance in Small and Medium Enterprises (SMEs) in Indonesia. The research method used was quantitative with data analysis using Partial Least Squares (PLS) version 3.0.The number of respondents was 170 from SME employees in Indonesia. The analysis shows that Organizational Culture has a strong positive influence on Employee Performance with a T-statistical value of 6.527 and a P value of 0.000, which indicates a very high statistical significance. The Work Environment was also proven to have a positive influence on Employee Performance with a T-statistical value of 4.478 and a P value of 0.000, which showed very high statistical significance, The relationship between Wage Level and Employee Performance showed weaker results with a T-statistical value of 1.776 and a P value of 0.076. This indicates that this relationship is not statistically significant at the conventional level of significance. Keywords: Organizational Culture, Work Environment, Wage LevelThe analysis shows that Organizational Culture has a strong positive influence on Employee Performance with a T-statistical value of 6.527 and a P value of 0.000, which indicates a very high statistical significance. The Work Environment was also proven to have a positive influence on Employee Performance with a T-statistical value of 4.478 and a P value of 0.000, which showed very high statistical significance, The relationship between Wage Level and Employee Performance showed weaker results with a T-statistical value of 1.776 and a P value of 0.076. This indicates that this relationship is not statistically significant at the conventional level of significance.